Pragmatic language disorders in hearing-impaired children and children with cochlear implants from the perspective of their teachers (Journal of the College of Basic Education, 2025)
The current research deals with pragmatic language disorder in hearing-impaired children and children with cochlear implants from the point of view of their teachers, as hearing-impaired children and their peers with cochlear implants may be at risk of developing pragmatic language disorder due to the type of disability they suffer from, and because hearing has a relationship with language, which It may be reflected in their ability to interact with others and use appropriate language in the social context. The researcher has formulated several objectives, which are:1- Measuring pragmatic language disorder in hearing-impaired children.2- Measuring pragmatic language disorder in children with cochlear implants.3- Measuring differences in the level of pragmatic language disorder in hearing-impaired children and children with cochlear implants.4- Measuring the differences in the level of pragmatic language disorder among hearing-impaired children and their peers with cochlear implants according to the gender variable (males - females). The current research was limited to hearing-impaired children and their peers with cochlear implants registered in Baghdad institutes (Karkh - Rusafa) for the academic year 2024-2025. The research sample was (200) children, including (100) hearing-impaired children, and (100) children with cochlear implants who were chosen randomly, and then (80) hearing-impaired children were chosen, including (40) males. (40) were female, and (80) Children with cochlear implants (40) male children and (40) female children to find differences in the level of pragmatic language disorder according to the gender variable. The researcher prepared a measure of pragmatic language disorder, following the psychometric steps in constructing the measures, and then the researcher applied the measure to Research sample: The results showed that hearing-impaired children and children with cochlear implants suffer from pragmatic language disorder There are statistically significant differences in the level of pragmatic language disorder in favor of hearing-impaired children, and there are statistically significant differences in the level of pragmatic language disorder according to the gender variable and in favor of males. To complement the relevant aspects, the researcher came up with a number of recommendations and proposals related to the topic of his research.